A Single Switch High Step-Up DC-DC Converter Based on Tri-Winding Coupled Inductor for Renewable Energy Applications. (28th October 2022) - Hosseinzadehlish, Mana; Hashemzadeh, Seyed Majid; Pourjafar, Saeed; Babaei, Ebrahim
Abstract : This article introduces a novel nonisolated single-switch high step-up DC-DC converter using a tri-winding coupled inductor (TWCL) for renewable energy applications such as PV systems. Also, the voltage multiplier cell (VMC) is used to attain a high voltage gain. The used VMC acts as a passive clamp circuit and reduces the voltage stress across the power switch. So, a low voltage-rated power switch can be used in the presented converter. The suggested topology uses only one power switch with low on-state resistance ( R DS-ON ), which leads to a simple control circuit and decreases the conduction losses. Highefficiency, operating with low duty cycle, low peak voltage over semiconductor elements, low turns ratio, the number of the coupled inductor, and high voltage conversion ratio are the significant benefits of the recommended DC-DC converter. To show the achievement of the presented structure, operational mode principles, steady-state, efficiency calculations, and comparison results are provided. Finally, a 120 W experimental prototype with 200 V output voltage and 50 kHz switching frequency is built to prove the usefulness of the suggested high step-up converter. The efficiency is measured 92.11% at rated power.